The Thigh of Its Mother: The Fetus and the Subordinated Subject in the Babylonian Talmud - Ronis, Sara (Journal of the American Academy of Religion, 2022)
Modern discussions of abortion in Jewish thought often invoke the Talmudic phrase "ubar yerekh imo," the fetus is the thigh of its mother. This article examines the ten instances in which the phrase first appears in the Babylonian Talmud. I demonstrate that the rabbis of Late Antique Sasanian Babylonia deploy the phrase in two specific contexts: discussions of the sanctification, criminalization, or sale of non-human animal fetuses, and discussions of the sale and manumission of the fetuses of enslaved people. Drawing on insights from animal studies and studies of slavery, I argue that this phrase illuminates how the rabbis think with the fetus to value some lives over others in a world reliant on the exploitation of enslaved humans and animals, and compare this approach with that of the Roman jurist Ulpian. Ultimately, I shed light on ancient rabbinic anthropologies of the human body and the body politic.